Ground Temperatures and Permafrost Warming from Forest to Tundra, Tuktoyaktuk Coastlands and Anderson Plain, NWT, Canada - Kokelj, S.V. (S. V.); Palmer, M.J. (M. J.); Lantz, T.C. (T. C.); Burn, C. (Christopher R.) (Permafrost and Periglacial Processes, 2017)
Annual mean ground temperatures (Tg) decline northward from approximately −3.0°C in the boreal forest to −7.0°C in dwarf-shrub tundra in the Tuktoyuktuk Coastlands and Anderson Plain, NWT, Canada. The latitudinal decrease in Tg from forest to tundra is accompanied by an increase in the range of values measured in the central, tall-shrub tundra zone. Field measurements from 124 sites across this ecotone indicate that in undisturbed terrain Tg may approach 0°C in the forest and −4°C in dwarf-shrub tundra. The greatest range of local variation in Tg (~7°C) was observed in the tall-shrub transition zone. Undisturbed terrain units with relatively high Tg include riparian areas and slopes with drifting snow, saturated soils in polygonal peatlands and areas near lakes. Across the region, the warmest permafrost is associated with disturbances such as thaw slumps, drained lakes, areas burned by wildfires, drilling-mud sumps and roadsides. Soil saturation following terrain subsidence may increase the latent heat content of the active layer, while increases in snow depth decrease the rate of ground heat loss in autumn and winter. Such disturbances increase freezeback durat